New controller implementation and force sensor instrumentation of a puma robot towards uncertainty identification. - Chua, Alvin
This paper presents a new design and implementation of an interrupt driven control system for a Puma 560 robot, which will provide the facility to implement true real-time control on a PC. In the new controller design, the paper discusses the new hardware configuration, control system adopted, and software design implemented for the Puma robot. Also, a controller tuning procedure was developed for robot joint dc motors to avoid oscillations and overshoot in their response. The inverse kinematics implementation to the software controller will also be explained. Finally, the paper also describes a force sensor integration that will be used together with the new controller for uncertainty (error) identification task. This will include a discussion on the force sensor and its use, the safety system including watchdog timer and crash protector and some experiments to test the effectiveness of the force sensor in uncertainty (error) identification.